2022
DOI: 10.12709/mest.10.10.01.01
|View full text |Cite
|
Sign up to set email alerts
|

LEAN MANUFACTURING vs COVID-19

Abstract: During the COVID-19 pandemic, companies coped and still must deal with uncertainty greater than ever. Due to the unpredictability of consumer demand, the incredible growth in demand for certain products, dramatic fluctuations in supply chains, and general economic instability, the future still looks uncertain. It is up to the manufacturers to determine how things will be sorted out in the new normality, i.e., which changes will be long-lasting or even permanent. Lean production has emerged in recent decades as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Seleem et al (2020) developed a path for lean manufacturing for industrial businesses based on the limits of the company and the predetermined strategic goals. A positive feedback is presented by Cekerevac et al (2022) where it is shown that lean production affirmatively added value to the companies in the post-COVID-19 period with some examples as evidence. Obstacles and enablers of circular supply chain management were highlighted by Khan and Ali (2022), while Patwa et al (2021) investigated the implementation of circular economy in emerging economies.…”
Section: Existing Methods and Rationale Behind This Studymentioning
confidence: 99%
“…Seleem et al (2020) developed a path for lean manufacturing for industrial businesses based on the limits of the company and the predetermined strategic goals. A positive feedback is presented by Cekerevac et al (2022) where it is shown that lean production affirmatively added value to the companies in the post-COVID-19 period with some examples as evidence. Obstacles and enablers of circular supply chain management were highlighted by Khan and Ali (2022), while Patwa et al (2021) investigated the implementation of circular economy in emerging economies.…”
Section: Existing Methods and Rationale Behind This Studymentioning
confidence: 99%
“…The COVID-19 pandemic and the massive transition to remote work in almost all countries have stimulated digital transformation processes and increased costs for individual digital solutions that allow organizing remote interaction between employees. (Cekerevac, Dvorak, & Prigoda, 2022) Most global companies are actively considering the ecosystem business model currently since in the last 5 years it is these companies that have shown the greatest growth in value (Fig. 2).…”
Section: The Role Of Digitalization In the Economymentioning
confidence: 99%
“…An appropriate level of financial literacy helps a person to accumulate economically valuable knowledge, makes financially behavior more productive, and helps to improve the standard of living of citizens by rationalizing the family budget, developing the ability to manage finances and, as a result, contributes to the growth of the well-being of the population. (Cekerevac, Dvorak, & Prigoda, 2022)…”
Section: Modern Financial Literacymentioning
confidence: 99%